Concept of Verbal Cognition According to the Indian Schools of Thought - Kar, N.C. (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The world is conceived by language and without it, the whole world would have become utter darkness. Languages are syntactic, the words and its substances and their relationship are the basis of sentences. In such a situation, a thorough analysis of the relationship between the word and its substances becomes indispensable for a better understanding of the issue. The significance of language and the process of its understanding has become a priority among the philosophers since time immemorial. Different schools of philosophical thought in India have taken this issue seriously without any exception. The discourse among the scholars of these schools of thought has presented three different significant theories i.e. (i) the meaning of the verbal root is prominent, (ii) meaning of the noun in nominal case ending is the prominent, and (iii) the meaning of the personal suffixes are the prominent in understanding the meaning of sentences. This difference emerges because each system starts with certain presuppositions with which others do not agree in toto. This paper is an attempt to explore and examine these different ideas of verbal understanding by different schools of thought for a better understanding of the subject.